Dermoid cyst located in the floor of the mouth: case report - Juliana Portes de Oliveira; Danielle Castex Conde; Alexandre Moraes (Associação Brasileira de Odontologia, 2018)
Objective: to report a case of dermoid cyst addressing the criteria of clinical and histopathological diagnosis. Case report: seventeen-year-old patient with increased volume in the floor of the mouth. A biopsy was performed and the diagnosis was dermoid cyst. Intraoral enucleation of the lesion was performed, and no recurrence was observed after an 18-month follow-up. Conclusion: although some clinical features and imaging tests suggest this diagnosis, only histopathological examination can confirm it. Thus, it is important that the dental surgeon knows the lesion and possible morbidities that it can cause, enabling a precise diagnosis and appropriate behavior, thus benefiting the patient.